Trans-arterial chemoembolization with degradable starch microspheres (DSM-TACE) versus selective internal radiation therapy (SIRT) in multifocal hepatocellular carcinoma. (March 2021) - Auer, Timo A; Jonczyk, Martin; Collettini, Federico; Marth, Adrian; Wieners, Gero; Hamm, Bernd; Gebauer, Bernhard
Background: To date there is no therapy consensus in patients with multifocal hepatocellular carcinoma (mHCC). Purpose: To compare outcome of trans-arterial chemoembolization (TACE) with degradable starch microspheres (DSM-TACE) versus selective internal radiation therapy (SIRT) in mHCC. Material and Methods: In this single-center study, 36 patients without portal vein invasion, treated between May 2014 and May 2018, were enrolled retrospectively. Eighteen consecutive patients received DSM-TACE and were matched by age, gender, BCLC stage, Child-Pugh status, and tumor volume and 18 patients underwent SIRT. Overall survival (OS), progression-free survival (PFS), and local tumor control (LTC) were evaluated. Toxicity profiles for both therapies were also evaluated and compared. Results: In the entire collective, median OS was 9.5, PFS 5.0, and LTC 5.5 months. Subgroup analysis revealed an OS of 9.5 months in both groups ( P  = 0.621). PFS was 6 months for the SIRT and 4 months for the DSM-TACE cohort ( P  = 0.065). Although not significantly, LTC was lower (4 months) in the SIRT compared to the DSM-TACE cohort (7 months; P  = 0.391). When DSM-TACE was performed ≥3 times (n = 11), OS increased, however without statistical difference compared to SIRT, to 11 months, PFS to 7 months, and LTC to 7 months. When DSM-TACE was performed <3 times (n = 7), OS, PFS, and LTC decreased (5 months, P  = 0.333; 2 months, P  = 0.047; 2 months, P  = 0.47). Toxicity profiles and adverse event analysis only revealed a significant difference for nausea and vomiting (more frequent in the SIRT cohort, P  = 0.015), while no other parameter showed a significant difference ( P  > 0.05). Conclusion: DSM-TACE might be an alternative to SIRT in multifocal HCC patients as OS, PFS, and LTC did not differ significantly and toxicity profiles seem to be comparable.